The project of a transcendental phenomenology that is non-idealist - Vargas Bejarano, Julio César (Estudios de Filosofía, 2013)
In Ideas I, phenomenology is presented as “transcendental idealism.” This research shows that five years earlier, in 1908, Husserl agreed to the formulation of a “transcendental idealism”, but from a different path than that of Ideas I. In 1913 and until 1921, the founder of phenomenology takes up and develops the initial foundation of “transcendental idealism.” We present the main features of this “demonstration” of “transcendental idealism” and ponder up to what point it opens the possibility of a “methodological transcendentalism” path to a non-idealistic transcendental philosophy.